La pobreza en la prensa : palabras clave en los diarios de Argentina, Brasil, Colombia y México - Chiquito, Ana Beatriz; Rojas Mayer, Elena; Llull, Gabriela; Pinardi, Carolina; Cortês, Lara Barbosa Quadros (CLACSO, 2019)
As the reader will notice, this publication has been built from very diverse fields of knowledge and has been an attempt to put into dialogue different theoretical perspectives to account for the words and notions with which poverty is conceptualized in the press of four major Latin American countries. The heterogeneity in the approaches and modes of treatment of the problem constitutes, from our perspective, one of the main strengths of this work. We believe that the complexity of the phenomena we address requires approaches that avoid simplifications and reductionisms and account for the ideological and epistemological debates around what constitutes the most relevant problem in our countries.